Proposed new interior design scheme of Mercedes-Benz Exclusive Club for cycle & carriage Bintang Berhad at Suasana Sentral Condo, Kuala Lumpur Sentral. / Nor Salasiah Monil - Monil, Nor Salasiah (Faculty of Architecture, Planning and Surveying, 2005)
My final project is to Proposed Upgrading of Mercedes Benz Members Exclusive Club for Cycle & Carriage Bintang Berhad. Object of the project is to create one facility for the owner of the Mercedes Benz cars. Beside that, purpose to built the club is to represent more about Mercedes Benz cars in Malaysia. The club also become as a place for gathering and do the function such as launching new model, club activities and family function. With all the research, this club can be the first exclusive car club house with latest sophisticated facilities inside. All the research is base on the existing car club in Malaysia. The existing club in Malaysia seldom have car club house or place for any comity activities, such as meeting or club function. Despite on that with this club can make Mercedes Benz members enjoy the activities inside the club. Opening the club are not only focus people in Malaysia but also permanent or temporary resident who live in Malaysia. This club also will represent about modernist Malaysia to the global.